(untitled) (Journal of Fatima Jinnah Medical University, 2019)
Diabetes mellitus (DM) has become a universal health problem which is driven by increased caloric consumption resulting in obesity and other complications developing over the years.1 The World Health Organization (WHO) estimates that >422 million people worldwide are suffering from diabetes.2 Microvascular complications of DM like, nephropathy, retinopathy and neuropathy are responsible for increasing morbidity and mortality, and affected patients add greatly to healthcare costs.2